2017
DOI: 10.1007/s10384-017-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlative factors’ analysis of postural-related ocular cyclotorsion with image-guided system

Abstract: Cyclotorsion orientation seems to be correlated only with eye laterality. None of the other investigated factors, including age, gender, eye axial length, BCVA, astigmatism degree, astigmatism axis and anesthesia seems to affect cyclotorsion orientation or degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…These facts probably led to the difference of the mean cyclotorsion between right and left eyes (1.83 and 0.18 degrees, respectively), although not statistically significant. Zhao et al 25 reported that the difference of cyclotorsion might be correlated with eye laterality, and excyclotorsion was predominant in right eyes, whereas incyclotorsion was predominant in left eyes, which was consistent with our results. As the reason for the findings, they focused on a common knowledge that in most people the right eye was the dominant eye, and hypothesized that the muscles of the dominant eye might be stronger than those of the other eye, resulting in the bilateral difference.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These facts probably led to the difference of the mean cyclotorsion between right and left eyes (1.83 and 0.18 degrees, respectively), although not statistically significant. Zhao et al 25 reported that the difference of cyclotorsion might be correlated with eye laterality, and excyclotorsion was predominant in right eyes, whereas incyclotorsion was predominant in left eyes, which was consistent with our results. As the reason for the findings, they focused on a common knowledge that in most people the right eye was the dominant eye, and hypothesized that the muscles of the dominant eye might be stronger than those of the other eye, resulting in the bilateral difference.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, accurately investigating posture-related cyclotorsion and exploring the predictive factors among cataract patients are clinically essential. Many studies have shown the degree and direction of cyclotorsion by using an ocular registration system [14][15][16][17][18][19][20][21][22][23][24][25] ; however, nearly all of these studies have targeted only normal individuals or patients undergoing corneal refractive surgeries such as laser in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK). The background (e.g., age and preoperative visual acuity) of patients undergoing excimer laser refractive surgery is completely different from that of cataract patients; therefore, the elucidation of posture-related cyclotorsion of patients with cataract is desired.…”
mentioning
confidence: 99%
“…Varying proportions of cyclotorsion orientation have been reported in different series and several reports in the literature have mentioned the predominance of incyclotorsion or excyclotorsion in eyes undergoing ocular surgery [9101112]. Zhao et al [9] stated that incyclotorsion occurs more prevalently in left eyes and excyclotorsion occurs more prevalently in right eyes, which are the dominant eye for most subjects. However, various studies have reported no association between dominant eye and excyclotorsional movement.…”
Section: Discussionmentioning
confidence: 99%
“…Hummel et al [12] reported that incyclotorsion occurs more prevalently in both of the right and the left eyes. Zhao et al [9] also reported that several factors, including age, sex, visual acuity, astigmatism degree or axis, and axial length, are not associated with the orientation of cyclotorsion. In the current study, incyclotorsion was more common than excyclotorsion and no demographic or clinical features were found to be related to cyclotorsion orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that the PVDF ultrasonic sensor has a lower resonant Q value, and the signal rise and decay time are shorter than the conventional piezoelectric crystal ultrasonic sensor at the time of reception, and this characteristic makes the received ultrasonic signal have higher resolution and is suitable for positioning applications. Moreover, the PVDF sensor is an omnidirectional sensor that does not have to consider the sensor angle problem in the circuit [28].…”
Section: Figure 5 Schematic Diagram Of the Circuit Generated By The mentioning
confidence: 99%